HUBUNGAN LAMA PENGGUNAAN ALAT KONTRASEPSI ORAL (PIL KB) DAN INTRAUTERINE DEVICE (IUD) TERHADAP RESIKO KANKER SERVIKS DI PUSKESMAS NGORESAN SURAKARTA - Innez Karunia Mustikarani (Jurnal Keperawatan Malang, 2020)
Cervical cancer is the second most common cancer after breast cancer in women by 371,000 new cases diagnosed annually or 9.8% of all female cancers, where 7.8% occur in developing countries. One of the most appropriate tests to determine the occurrence of cervical cancer is to use the IVA test. The purpose of this study was to discover the relationship between the use of oral contraceptives (birth control pills) and intrauterine devices (IUD) with the risk of cervical cancer at PuskesmasNgoresan Surakarta. This study used a retrospective cohort quantitative method with 71 respondents where the youngest age was 18 years and the oldest was 32 years. The bivariate analysis applied the ETA test. The bivariate result was 1,000 at Puskesmas Ngoresan Surakarta. This study concluded that there is a strong correlation between birth control pills and IUDs on the risk of cervical cancer.